Strategi Guru Pendidikan Agama Islam dalam Meningkatkan Kedisiplinan Ibadah Siswa Melalui Pembiasaan Shalat Dhuha - Alfin Syam Ilyas; Zainul Arifin; Aminatuz Zahroh (Sekolah Tinggi Teologi Injili dan Kejuruan (STTIK) Kupang, 2026)
This study aims to analyze the strategies used by Islamic Education teachers to improve student discipline in worship through the habit of performing the dhuha prayer at the PKBM PNF KBRI Kuala Lumpur, Malaysia. This study used a qualitative approach with a case study design. Data were obtained through observation, in-depth interviews, and documentation, then analyzed interactively to produce research findings. The results showed that the strategies applied by teachers through exemplary behavior, continuous guidance and supervision, religious motivation, and the integration of the dhuha prayer into the school's daily schedule were effective in shaping students' worship discipline. This discipline is reflected in the increased punctuality, regularity, and consistency of students in performing the dhuha prayer as a conscious habit. These findings confirm that the habit of performing the dhuha prayer, which is managed systematically and contextually by Islamic Education teachers, plays an important role in fostering students' worship discipline in non-formal educational institutions.